Pelaksanaan Pembelajaran Wudhu dengan Media Gambar bagi Anak Usia Dini Tadika Al Fikh Orcard Pendamar Indah 2 Selangor - Avivah Aldiansyah Barutu; Rizka Harfiani (Journal on Education, 2023)
This study aims to describe the implementation of ablution learning with media images in early childhood Al Fikh Orchard Pendamar Indah 2 Selangor Malaysia. This research uses a descriptive qualitative approach. Data collection techniques used are observation, interviews and documentation. Implementation of ablution learning with media images where the teacher directly introduces each step in ablution from the initial stage to the end using media images in the form of posters. The implementation of ablution learning is carried out repeatedly every week so that children can understand and practice it directly. From the findings of observations made by researchers, there were several children who had not been able to practice ablution but were very enthusiastic in learning ablution and some children had been able to practice ablution according to the sunnah of the Prophet in ablution.